(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
Many years after the world wars, there is now a growing recognition of the importance of African Traditional Religion (ATR) for designing development programs and projects. However, the involvement of the religion of the indigenous people of Africa is not given the attention it requires. This paper therefore aims at presenting African traditional religion’s voice in this important discourse by using it to create a measure for economic development. Despite its suffering from stereotyping African traditional religion continues to play a critical role in the lives of the traditional Africans. The issue of economic development, poverty eradication and wealth creation is not easy to define. The divergent theories on it points to this fact. The traditional African understanding of development, however is derived from their religious world views. The institution of chieftaincy, gerontocracy, institution of taboos, kingship ties and their attitude towards nature are some of the major development mechanisms among the Africans. Despite the devastating threats these mechanisms are undergoing today, the potentials of these indigenous mechanisms for development are not in doubt, hence the need for this work. The work recommends that African Traditional Religion remains a major contributing factor to poverty alleviation and wealth creation in Ikwerre ethnic nationalities